Multivariate analysis of 3D ToF-SIMS images: method validation and application to cultured neuronal networks - Van Nuffel, Sebastiaan; Parmenter, Christopher D.J.; Scurr, David J.; Russell, Noah A.; Zelzer, Mischa (Royal Society of Chemistry, 2015)
Advanced data analysis tools are crucial for the application of ToF-SIMS analysis to biological samples. Here, we demonstrate that by using a training set approach principal components analysis (PCA) can be performed on large 3D ToF-SIMS images of neuronal cell cultures. The method readily provides access to sample component information and significantly improves the images’ signal-to-noise ratio (SNR).